"Acute" silicosis at the 1930 Johannesburg Conference on silicosis and in its aftermath: Controversies over a distinct entity later recognized as silicoproteinosis. Issue 1 (15th June 2015) - Blanc, Paul D.
Abstract : Background: Very rapidly progressive "acute silicosis" was observed prior to the 1930 International Labour Office Conference on silicosis, but its clinical significance and pathologic relationship to classic silica caused pneumoconiosis were not settled. Methods: Textual analysis of the 1930 Conference proceedings identified data relevant to rapidly progressive silicosis. Standard bibliographic searches identified relevant biomedical literature dating from before and after the Conference. Results: The 1930 Johannesburg Conference contained descriptions of acute silicosis, especially in the abrasive powders industry, but acute silica‐related lung disease did not conform to a three‐stage disease model in which tuberculosis supra‐infection caused advanced disease, a model accepted at the Conference. Over following decades, additional reports appeared of rapidly progressive silicosis, unrelated to tuberculosis. Pulmonary alveolar proteinosis was identified only in 1958. Conclusions: Adoption by the 1930 Johannesburg Conference of a classification scheme into which acute rapidly progressive disease unrelated to tuberculosis fitted poorly may have impeded the understanding of acute silicosis and its importance. Am. J. Ind. Med. 58:S39–S47, 2015. © 2015 Wiley Periodicals, Inc.